Repeated exposition to mercury (II) chloride enhances susceptibility to s. schenckii sensu stricto infection in mice - Batista-Duharte, Alexander [UNESP]; Téllez-Martínez, Damiana [UNESP]; Jellmayer, Juliana Aparecida [UNESP]; Fuentes, Deivys Leandro Portuondo [UNESP]; Polesi, Marisa Campos [UNESP]; Baviera, Amanda Martins [UNESP]; Carlos, Iracilda Zeppone [UNESP] (MDPI, 2018)
Sporotrichosis is a subcutaneous mycosis that has re-emerged in several tropical and subtropical regions over the last decades. Growing findings suggest that the interplay of host, pathogen, and environment has a determinant effect on the diversity, local distribution, and virulence of Sporothrix schenckii sensu lato, the etiologic agent. Among the environmental factors, we have studied the potential role of repeated exposures to mercury (Hg), a known immunotoxic xenobiotic that is widely used in gold mining regions where sporotrichosis outbreaks are frequently reported. In this study, male Swiss mice received subcutaneous injections of either 300 or 1200 µg/kg of mercury (II) chloride (HgCl2) for 14 days, three times a week. A control group was injected with the vehicle Phosphate Buffered Saline (PBS). Treatment with HgCl2 impaired several immunologic parameters that are involved in host response to Sporothrix infection, such as the production of TNFα, IL-1, and nitric oxide by macrophages, and Th1/Th2/Th17 populations and their respective cytokines. The consequences of these effects on the host resistance to S. schenckii infection were subsequently evaluated. Hg-exposed mice exhibited a higher fungal load in the fungal inoculation site associated to systemic dissemination to spleen and liver on 14 days post-infection and a higher production of specific IgG1 and mild reduction of IgG2a. These findings suggest that repeated exposition to Hg enhances susceptibility to S. schenckii infection in mice and can be a factor associated to sporotrichosis outbreaks in endemic and highly Hg-polluted areas.
Keywords: Immunotoxicity; Mercury (ii) chloride; Sporothrix schenckii infection; Sporotrichosis